RENALASE PROTECTS AGAINST SALT-INDUCED KIDNEY INJURY AND INFLAMMATION BY INHIBITING THE ACTIVATION OF THE AKT-1 SIGNALING PATHWAYS. (April 2021) - Wang, Keke; Wang, Yang; Yuan, Yue; Ma, Qiong; Yan, Yu; Liao, Yueyuan; Mu, Jianjun
Abstract : Objective: An excess of dietary salt is the most common environmental factor that contributes to the development of hypertension leading to renal pathologies. Renalase (RNLS), a novel secreted flavoprotein with oxidoreductase activity, functions as a survival factor and promotes cell and organ survival. Previous evidence showed that recombinant renalase exerts powerful hypotensive effects and ameliorates renal interstitial fibrosis in rodents. In this study, we evaluated the potential protective role of renalase and underlying mechanisms in salt-induced kidney injury and inflammation. Design and method: In vitro, human proximal renal tubular epithelial (HK-2) cells were treated with normal salt or high salt (40 mM NaCl) for 24 hours, receiving recombinant renalase (25ug/mL) or vehicle. In vivo, Dahl salt-sensitive (DS) rats and renalase knockout mice were placed on normal (0.8% NaCl) or high salt (8% NaCl) diet with or without renalase (1 mg/kg) for 4 weeks. Results: In vitro, renalase decreased the phosphorylation levels of protein kinase B (Akt-1), leading to a reduction in the mRNA expression of pro-inflammatory cytokines and oxidative stress induced by high salt. And when knockdown the channel plasma membrane calcium ATPase (PMCA4b) in HK-2 cells, the inflammation and oxidative stress levels induced by high-salt decreased. In DS rats, high salt diet significantly increased the blood pressure and the 24 h urinary sodium excretion. Furthermore, renal inflammation and fibrosis of high salt group were more severe compared to normal salt diet group. Administration of recombinant human renalase reduced kidney inflammation through inhibition of Akt-1 pathway. Similarly, genetic depletion of renalase in mice (renalase knockout) exacerbated kidney injury in animals with high salt diet. Treatment with recombinant renalase significantly decreased the kidney inflammation through inhibition Akt-1 expression. Conclusions: Our study provides the first evidence that renalase can ameliorate kidney injury and inflammation through inhibition of the Akt-1 pathway. These results suggest that renalase has potential renoprotective effects in renal injury and inflammation and may be an effective agent for slowing kidney damage.